Water-based acrylic resin-based rotor antirust agent and processing method thereof

By preparing rust inhibitor A and rust inhibitor B and participating in polymerization in acrylic resin, the problem of poor rust prevention effect of traditional water-based acrylic resin-based rust inhibitors in natural environments was solved, and more lasting and reliable rust prevention protection was achieved.

CN120623867AActive Publication Date: 2025-09-12DONGGUAN YINGFEITE LUBRICATION TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202511023930.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-24
Publication Date
2025-09-12
Estimated Expiration
2045-07-24

AI Technical Summary

Technical Problem

Traditional water-based acrylic resin-based rust inhibitors have limited anti-rust effects in natural environments or specific working conditions, making it difficult to meet long-term rust prevention needs. They also have problems with water resistance, flash rusting, and poor wet adhesion to metals.

Method used

Rust inhibitor A and rust inhibitor B are prepared. Rust inhibitor A is synthesized from oleic acid and hydroxyethylethylenediamine to form 1-(2-hydroxyethyl)-2-oleic acid imidazoline, which reacts with perfluoropolyether carboxylic acid. Rust inhibitor B is synthesized from tannic acid and glycidyl methacrylate and combined with carbon nanotubes. The two are polymerized in acrylic resin to form a high-strength adsorption film.

Benefits of technology

It significantly improves the anti-rust effect of the rust inhibitor and the strength of the adsorption film, and can provide long-lasting and reliable corrosion protection in different environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of antirust agents, in particular to a water-based acrylic resin-based rotor antirust agent and a processing method thereof. The water-based acrylic resin-based rotor antirust agent is prepared from the following raw materials in parts by weight: 50 to 60 parts of modified acrylic resin, 10 to 20 parts of deionized water, 0.1 to 0.2 part of dimethylethanolamine, 4 to 6 parts of barium sulfate, 10 to 15 parts of mica iron oxide, 0.1 to 0.3 part of dispersing agent, 0.1 to 0.2 part of defoaming agent, 0.1 to 0.3 part of flatting agent and 1 to 3 parts of coalescing agent. The antirust agent A and the antirust agent B are combined in the water-based acrylic resin to play a synergistic role, so that the water-based acrylic resin-based rotor antirust agent with excellent antirust property and adhesive force is prepared, and meanwhile, the water-based acrylic resin-based rotor antirust agent has excellent corrosion resistance and hydrophobicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rust inhibitors, in particular to a water-based acrylic resin-based rotor rust inhibitor and a processing method thereof. Background Art

[0002] With the rapid development of industry, metal materials have been widely used in various fields. As a key component in many mechanical devices, rotors are crucial for rust prevention. Traditional rust inhibitors are mostly solvent-based. While they offer good protection, their release of volatile organic compounds (VOCs) has serious impacts on the environment and human health, leading to their increasing use restrictions. In contrast, water-based acrylic resin-based rust inhibitors, primarily water-based and free of harmful substances such as organic solvents and heavy metals, have attracted widespread attention due to their environmental friendliness, safety, low cost, and easy residue removal.

[0003] However, some water-based acrylic resin-based rust inhibitors have limited rust prevention effectiveness in natural environments or under specific operating conditions, making them difficult to meet long-term rust prevention requirements. For example, some rust inhibitors only maintain their effectiveness for a few weeks in natural environments, making them inadequate for long-term rotor rust prevention in outdoor or harsh environments. To address the challenges of acrylic emulsions in terms of water resistance, flash rusting, and poor wet metal adhesion, we have developed a water-based acrylic resin-based rotor rust inhibitor and its processing method. Summary of the Invention

[0004] The object of the present invention is to provide a water-based acrylic resin-based rotor rust inhibitor and a processing method thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions: A method for processing a water-based acrylic resin-based rotor rust inhibitor comprises the following steps: Step 1: 1-(2-hydroxyethyl)-2-oleic acid imidazoline, perfluoropolyether carboxylic acid and toluene are uniformly mixed, p-toluenesulfonic acid and hydroquinone are added, and the mixture is reacted at 115-120° C. for 5-7 hours, and then distilled under reduced pressure to obtain rust inhibitor A; Step 2: Disperse double-bond tannic acid in deionized water, stir for 10-20 minutes, add a mixed solution of phosphoric acid and a penetrant, and stir evenly to obtain a modified tannic acid solution; disperse carbon nanotubes in the modified tannic acid solution, ultrasonically disperse for 2-3 hours, centrifuge, and dry to obtain a rust inhibitor B; Step 3: Styrene, acrylic acid, rust inhibitor A, rust inhibitor B, 2-hydroxyethyl methacrylate, methyl methacrylate and butyl acrylate are mixed evenly, and ammonium persulfate is added and mixed evenly to obtain a mixture; deionized water and a composite emulsifier are mixed evenly, the temperature is raised to 75-80° C., 1 / 3 of the mixture by mass is added dropwise, the mixture is added over 30-40 minutes, and the reaction is carried out for 0.5-1.0 hours; the remaining mixture is added dropwise over 2-3 hours, the reaction is carried out at 85-90° C. for 2-3 hours, the temperature is lowered to 45-55° C., triethylamine is used for neutralization, and filtering is carried out to obtain a modified acrylic resin; Step 4: Evenly mix the modified acrylic resin and deionized water, add dimethylethanolamine, dispersant, defoaming agent, leveling agent, film-forming aid, barium sulfate, and mica iron oxide, and mix evenly to obtain a water-based acrylic resin-based rotor rust inhibitor.

[0006] Furthermore, in step 1, the mass ratio of the 1-(2-hydroxyethyl)-2-oleic acid imidazoline, perfluoropolyether carboxylic acid, and toluene is 1:(1.5-3.0):(3-5).

[0007] Furthermore, the preparation steps of the 1-(2-hydroxyethyl)-2-oleic acid imidazoline are as follows: oleic acid, hydroxyethylethylenediamine and xylene are uniformly mixed, reacted at 150-160° C. for 5-7 hours, and then continued to heat to 210-220° C. for 3-5 hours to obtain 1-(2-hydroxyethyl)-2-oleic acid imidazoline.

[0008] Furthermore, the mass ratio of oleic acid, hydroxyethylethylenediamine and xylene is 1: (0.4-0.5): (0.7-1.0).

[0009] Furthermore, in step 1, the masses of p-toluenesulfonic acid and hydroquinone are 3-5% and 0.1-0.3% of the total mass of 1-(2-hydroxyethyl)-2-oleic acid imidazoline and perfluoropolyether carboxylic acid, respectively.

[0010] Furthermore, in step 2, the mass ratio of the double-bond tannic acid, deionized water, phosphoric acid and penetrant is 1: (25-50): (1-2): (0.01-0.03).

[0011] Furthermore, in step 2, the preparation steps of the double-bond tannic acid are as follows: tannic acid, triphenylphosphine, hydroquinone, and ethyl acetate are evenly mixed, glycidyl methacrylate is added, and the mixture is reacted at 85-95° C. for 22-24 hours. After purification and drying, tannic acid containing a double bond is obtained.

[0012] Furthermore, the mass ratio of the tannic acid, triphenylphosphine, hydroquinone, ethyl acetate and glycidyl methacrylate is 1: (0.05-0.07): (0.003-0.005): (2-4): (2-3).

[0013] Furthermore, in step 2, the mass ratio of the carbon nanotubes to the modified tannic acid solution is 1:(30-50).

[0014] Furthermore, in step three, the amounts of each component are as follows: 8-12 parts of styrene, 2-4 parts of acrylic acid, 4-6 parts of rust inhibitor A, 3-5 parts of rust inhibitor B, 10-15 parts of 2-hydroxyethyl methacrylate, 5-8 parts of methyl methacrylate, 4-6 parts of butyl acrylate, 1-3 parts of ammonium persulfate, 50-70 parts of deionized water, and 0.2-0.6 parts of composite emulsifier.

[0015] Furthermore, the composite emulsifier is prepared by uniformly mixing sodium lauryl sulfate and OP-10 in a mass ratio of 1:(1-2).

[0016] Furthermore, the corrosion-resistant coating includes the following raw materials: by weight, 50-60 parts of modified acrylic resin, 10-20 parts of deionized water, 0.1-0.2 parts of dimethylethanolamine, 4-6 parts of barium sulfate, 10-15 parts of mica iron oxide, 0.1-0.3 parts of dispersant, 0.1-0.2 parts of defoaming agent, 0.1-0.3 parts of leveling agent, and 1-3 parts of film-forming aid.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a water-based acrylic resin-based rotor rust inhibitor and its processing method. Oleic acid and hydroxyethylethylenediamine are used to synthesize 1-(2-hydroxyethyl)-2-oleic acid imidazoline with a double bond, which is then reacted with perfluoropolyether carboxylic acid to obtain rust inhibitor A. The introduction of fluorinated segments imparts excellent hydrophobicity to the material. Simultaneously, the introduction of active double bonds and imidazoline structures significantly enhances the interaction between rust inhibitor A and the metal surface, thereby strengthening the strength of the adsorption film formed by the rust inhibitor on the metal surface. This improvement makes the rust prevention effect more durable and reliable, and can effectively resist corrosion.

[0018] Tannic acid (TA) is a macromolecular polyphenol compound with excellent anti-corrosion effect. Tannic acid with active double bonds was prepared by ring-opening reaction of tannic acid and glycidyl methacrylate (GMA). Not only did the corrosion inhibition and passivation capabilities of tannic acid itself be retained, but the combination of phosphoric acid and tannin significantly improved the rust prevention performance of the rotor and adsorbed it onto carbon nanotubes through π-π non-covalent bonding, resulting in rust inhibitor B. Both Rust Inhibitors A and B incorporate active double bonds into their molecules, enabling them to participate in the polymerization process of acrylic resin and chemically bond to the resin's molecular chain, producing a water-based acrylic resin. By combining Rust Inhibitors A and B in a water-based acrylic resin, their synergistic effect not only enhances the overall performance of the rust inhibitors but also better addresses corrosion challenges in diverse environments, providing more comprehensive protection. DETAILED DESCRIPTION

[0019] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0020] It should be noted that the raw materials involved in the present invention are purchased from manufacturers without any special restrictions, and illustratively include (in this embodiment) perfluoropolyether carboxylic acid: model P916413, provided by Shanghai MacLean Biochemical Technology Co., Ltd.; carbon nanotubes: multi-walled carbon nanotubes, model XFM13, provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; barium sulfate: particle size 1250 mesh, provided by Foshan Guicheng Technology Co., Ltd.; penetrant: isopropyl alcohol; mica iron oxide: particle size 400 mesh, provided by Changzhou Chenghua New Material Technology Co., Ltd.; dispersant: brand BYK190; defoaming agent: brand BYK012; leveling agent: brand Tego 410; film-forming aid: dipropylene glycol butyl ether.

[0021] The following parts are by mass unless otherwise specified.

[0022] Example 1: A method for processing a water-based acrylic resin-based rotor rust inhibitor, comprising the following steps: Step 1: 4 parts of oleic acid, 1.6 parts of hydroxyethylethylenediamine and 2.8 parts of xylene were mixed evenly, reacted at 150°C for 5 hours, and then the temperature was further increased to 210°C for 3 hours to obtain 1-(2-hydroxyethyl)-2-oleic acid imidazoline; 4 parts of 1-(2-hydroxyethyl)-2-oleic acid imidazoline, 6 parts of perfluoropolyether carboxylic acid and 12 parts of toluene were mixed evenly, 0.03 parts of p-toluenesulfonic acid and 0.001 parts of hydroquinone were added, and the mixture was reacted at 115° C. for 5 hours. After vacuum distillation, rust inhibitor A was obtained; Step 2: 3 parts of tannic acid, 0.15 parts of triphenylphosphine, 0.009 parts of hydroquinone, and 6 parts of ethyl acetate were mixed evenly, 6 parts of glycidyl methacrylate were added, and the mixture was reacted at 85°C for 22 hours. After purification and drying, tannic acid containing double bonds was obtained; Disperse 4 parts of double-bond tannic acid in 100 parts of deionized water, stir for 10 minutes, add a mixed solution of 4 parts of phosphoric acid and 0.04 parts of a penetrant, and stir evenly to obtain a modified tannic acid solution; disperse 3 parts of carbon nanotubes in 90 parts of the modified tannic acid solution, ultrasonically disperse for 2 hours, centrifuge, and dry to obtain a rust inhibitor B; Step 3: Evenly mix 8 parts of styrene, 2 parts of acrylic acid, 4 parts of rust inhibitor A, 3 parts of rust inhibitor B, 10 parts of 2-hydroxyethyl methacrylate, 5 parts of methyl methacrylate and 4 parts of butyl acrylate, add 1 part of ammonium persulfate and mix evenly to obtain a mixture; evenly mix 50 parts of deionized water and 0.2 parts of a composite emulsifier, heat to 75°C, dropwise add 1 / 3 of the mixture by mass, drip it over 30 minutes, and react for 0.5 hours; continue to dropwise add the remaining mixture over 2 hours, react at 85°C for 2 hours, cool to 45°C, neutralize with triethylamine, filter, and obtain a modified acrylic resin; the composite emulsifier is a mixture of sodium lauryl sulfate and OP-10 in a mass ratio of 1:1; Step 4: Mix 50 parts of modified acrylic resin and 10 parts of deionized water, add 0.1 parts of dimethylethanolamine, 0.1 parts of dispersant, 0.1 parts of defoaming agent, 0.1 parts of leveling agent, 1 part of film-forming aid, 4 parts of barium sulfate, and 10 parts of mica iron oxide and mix evenly to obtain a water-based acrylic resin-based rotor rust inhibitor.

[0023] Example 2: A method for processing a water-based acrylic resin-based rotor rust inhibitor, comprising the following steps: Step 1: 5 parts of oleic acid, 2.25 parts of hydroxyethylethylenediamine and 4 parts of xylene were mixed evenly, reacted at 155°C for 6 hours, and then the temperature was further increased to 215°C for 4 hours to obtain 1-(2-hydroxyethyl)-2-oleic acid imidazoline; 5 parts of 1-(2-hydroxyethyl)-2-oleic acid imidazoline, 10 parts of perfluoropolyether carboxylic acid and 20 parts of toluene were mixed evenly, 0.6 parts of p-toluenesulfonic acid and 0.03 parts of hydroquinone were added, and the mixture was reacted at 118°C for 6 hours. After vacuum distillation, rust inhibitor A was obtained; Step 2: 4 parts of tannic acid, 0.24 parts of triphenylphosphine, 0.016 parts of hydroquinone, and 12 parts of ethyl acetate were mixed evenly, 10 parts of glycidyl methacrylate were added, and the mixture was reacted at 90°C for 23 hours. After purification and drying, tannic acid containing double bonds was obtained; Disperse 4 parts of double-bond tannic acid in 160 parts of deionized water, stir for 15 minutes, add a mixed solution of 6 parts of phosphoric acid and 0.08 parts of a penetrant, and stir evenly to obtain a modified tannic acid solution; disperse 4 parts of carbon nanotubes in 160 parts of the modified tannic acid solution, ultrasonically disperse for 2.5 hours, centrifuge, and dry to obtain a rust inhibitor B; Step 3: Evenly mix 10 parts of styrene, 3 parts of acrylic acid, 5 parts of rust inhibitor A, 4 parts of rust inhibitor B, 12 parts of 2-hydroxyethyl methacrylate, 7 parts of methyl methacrylate and 5 parts of butyl acrylate, add 2 parts of ammonium persulfate and mix evenly to obtain a mixture; evenly mix 60 parts of deionized water and 0.4 parts of a composite emulsifier, heat to 78°C, dropwise add 1 / 3 of the mixture by mass, drip it over 35 minutes, and react for 0.8 hours; continue to dropwise add the remaining mixture, drip it over 2.5 hours, react at 88°C for 2.5 hours, cool to 50°C, neutralize with triethylamine, filter, and obtain a modified acrylic resin; the composite emulsifier is a mixture of sodium lauryl sulfate and OP-10 in a mass ratio of 1:1.5; Step 4: Mix 55 parts of modified acrylic resin and 15 parts of deionized water, add 0.15 parts of dimethylethanolamine, 0.2 parts of dispersant, 0.15 parts of defoaming agent, 0.2 parts of leveling agent, 2 parts of film-forming aid, 5 parts of barium sulfate, and 12 parts of mica iron oxide and mix evenly to obtain a water-based acrylic resin-based rotor rust inhibitor.

[0024] Example 3: A method for processing a water-based acrylic resin-based rotor rust inhibitor, comprising the following steps: Step 1: 6 parts of oleic acid, 3 parts of hydroxyethylethylenediamine and 6 parts of xylene are mixed evenly, reacted at 160°C for 7 hours, and then the temperature is further increased to 220°C for 5 hours to obtain 1-(2-hydroxyethyl)-2-oleic acid imidazoline; 6 parts of 1-(2-hydroxyethyl)-2-oleic acid imidazoline, 18 parts of perfluoropolyether carboxylic acid and 30 parts of toluene were mixed evenly, 1.2 parts of p-toluenesulfonic acid and 0.072 parts of hydroquinone were added, and the mixture was reacted at 120° C. for 7 hours. After vacuum distillation, rust inhibitor A was obtained; Step 2: 3 parts of tannic acid, 0.21 parts of triphenylphosphine, 0.015 parts of hydroquinone, and 12 parts of ethyl acetate were mixed evenly, 9 parts of glycidyl methacrylate were added, and the mixture was reacted at 95°C for 24 hours. After purification and drying, tannic acid containing double bonds was obtained; Disperse 3 parts of double-bond tannic acid in 150 parts of deionized water, stir for 20 minutes, add a mixed solution of 6 parts of phosphoric acid and 0.18 parts of a penetrant, and stir evenly to obtain a modified tannic acid solution; disperse 5 parts of carbon nanotubes in 150 parts of the modified tannic acid solution, ultrasonically disperse for 3 hours, centrifuge, and dry to obtain a rust inhibitor B; Step 3: Evenly mix 12 parts of styrene, 4 parts of acrylic acid, 6 parts of rust inhibitor A, 5 parts of rust inhibitor B, 15 parts of 2-hydroxyethyl methacrylate, 8 parts of methyl methacrylate and 6 parts of butyl acrylate, add 3 parts of ammonium persulfate and mix evenly to obtain a mixture; evenly mix 70 parts of deionized water and 0.6 parts of a composite emulsifier, heat to 80°C, dropwise add 1 / 3 of the mixture by mass, drip it over 40 minutes, and react for 1.0 hour; continue to dropwise add the remaining mixture over 3 hours, react at 90°C for 3 hours, cool to 55°C, neutralize with triethylamine, filter, and obtain a modified acrylic resin; the composite emulsifier is a mixture of sodium lauryl sulfate and OP-10 in a mass ratio of 1:2; Step 4: Mix 60 parts of modified acrylic resin and 20 parts of deionized water, add 0.2 parts of dimethylethanolamine, 0.3 parts of dispersant, 0.2 parts of defoaming agent, 0.3 parts of leveling agent, 3 parts of film-forming aid, 6 parts of barium sulfate, and 15 parts of mica iron oxide and mix evenly to obtain a water-based acrylic resin-based rotor rust inhibitor.

[0025] Comparative Example 1: A method for processing a water-based acrylic resin-based rotor rust inhibitor, comprising the following processes: Step 1: 4 parts of tannic acid, 0.24 parts of triphenylphosphine, 0.016 parts of hydroquinone, and 12 parts of ethyl acetate are mixed evenly, 10 parts of glycidyl methacrylate are added, and the mixture is reacted at 90°C for 23 hours. After purification and drying, tannic acid containing a double bond is obtained; Disperse 4 parts of double-bond tannic acid in 160 parts of deionized water, stir for 15 minutes, add a mixed solution of 6 parts of phosphoric acid and 0.08 parts of a penetrant, and stir evenly to obtain a modified tannic acid solution; disperse 4 parts of carbon nanotubes in 160 parts of the modified tannic acid solution, ultrasonically disperse for 2.5 hours, centrifuge, and dry to obtain a rust inhibitor B; Step 2: 10 parts of styrene, 3 parts of acrylic acid, 4 parts of rust inhibitor B, 12 parts of 2-hydroxyethyl methacrylate, 7 parts of methyl methacrylate and 5 parts of butyl acrylate are mixed evenly, and 2 parts of ammonium persulfate are added and mixed evenly to obtain a mixture; 60 parts of deionized water and 0.4 parts of a composite emulsifier are mixed evenly, the temperature is raised to 78°C, 1 / 3 of the mixture by mass is added dropwise, the mixture is dripped over 35 minutes, and the reaction is carried out for 0.8 hours; the remaining mixture is continued to be dripped over 2.5 hours, the reaction is carried out at 88°C for 2.5 hours, the temperature is lowered to 50°C, triethylamine is used for neutralization, and the modified acrylic resin is obtained by filtering; the composite emulsifier is a mixture of sodium lauryl sulfate and OP-10 in a mass ratio of 1:1.5; Step 4: 55 parts of modified acrylic resin and 15 parts of deionized water are mixed evenly, and 0.15 parts of dimethylethanolamine, 0.2 parts of dispersant, 0.15 parts of defoamer, 0.2 parts of leveling agent, 2 parts of film-forming aid, 5 parts of barium sulfate, and 12 parts of mica iron oxide are added and mixed evenly to obtain a water-based acrylic resin-based rotor rust inhibitor; Comparative Example 1 is based on Example 2. Rust inhibitor A is not introduced into Comparative Example 1, and the remaining process steps and reaction parameters are consistent with those of Example 2.

[0026] Comparative Example 2: A method for processing a water-based acrylic resin-based rotor rust inhibitor, comprising the following processes: Step 1: 5 parts of oleic acid, 2.25 parts of hydroxyethylethylenediamine and 4 parts of xylene were mixed evenly, reacted at 155°C for 6 hours, and then the temperature was further increased to 215°C for 4 hours to obtain 1-(2-hydroxyethyl)-2-oleic acid imidazoline; Step 2: 4 parts of tannic acid, 0.24 parts of triphenylphosphine, 0.016 parts of hydroquinone, and 12 parts of ethyl acetate were mixed evenly, 10 parts of glycidyl methacrylate were added, and the mixture was reacted at 90°C for 23 hours. After purification and drying, tannic acid containing double bonds was obtained; Disperse 4 parts of double-bond tannic acid in 160 parts of deionized water, stir for 15 minutes, add a mixed solution of 6 parts of phosphoric acid and 0.08 parts of a penetrant, and stir evenly to obtain a modified tannic acid solution; disperse 4 parts of carbon nanotubes in 160 parts of the modified tannic acid solution, ultrasonically disperse for 2.5 hours, centrifuge, and dry to obtain a rust inhibitor B; Step 3: 10 parts of styrene, 3 parts of acrylic acid, 5 parts of 1-(2-hydroxyethyl)-2-oleic acid imidazoline, 4 parts of rust inhibitor B, 12 parts of 2-hydroxyethyl methacrylate, 7 parts of methyl methacrylate and 5 parts of butyl acrylate are mixed evenly, and 2 parts of ammonium persulfate are added and mixed evenly to obtain a mixture; 60 parts of deionized water and 0.4 parts of a composite emulsifier are mixed evenly, the temperature is raised to 78°C, 1 / 3 of the mixture by mass is added dropwise, the mixture is dripped over 35 minutes, and the reaction is carried out for 0.8 hours; the remaining mixture is continued to be dripped over 2.5 hours, the mixture is reacted at 88°C for 2.5 hours, the temperature is lowered to 50°C, triethylamine is used for neutralization, and the modified acrylic resin is obtained by filtering; the composite emulsifier is a mixture of sodium lauryl sulfate and OP-10 in a mass ratio of 1:1.5; Step 4: 55 parts of modified acrylic resin and 15 parts of deionized water are mixed evenly, and 0.15 parts of dimethylethanolamine, 0.2 parts of dispersant, 0.15 parts of defoamer, 0.2 parts of leveling agent, 2 parts of film-forming aid, 5 parts of barium sulfate, and 12 parts of mica iron oxide are added and mixed evenly to obtain a water-based acrylic resin-based rotor rust inhibitor; Comparative Example 2 is based on Example 2. In Comparative Example 2, perfluoropolyether carboxylic acid is not introduced, and the rust inhibitor A is replaced by 1-(2-hydroxyethyl)-2-oleic acid imidazoline. The remaining process steps and reaction parameters are consistent with Example 2.

[0027] Comparative Example 3: A method for processing a water-based acrylic resin-based rotor rust inhibitor, comprising the following processes: Step 1: 5 parts of oleic acid, 2.25 parts of hydroxyethylethylenediamine and 4 parts of xylene were mixed evenly, reacted at 155°C for 6 hours, and then the temperature was further increased to 215°C for 4 hours to obtain 1-(2-hydroxyethyl)-2-oleic acid imidazoline; 5 parts of 1-(2-hydroxyethyl)-2-oleic acid imidazoline, 10 parts of perfluoropolyether carboxylic acid and 20 parts of toluene were mixed evenly, 0.6 parts of p-toluenesulfonic acid and 0.03 parts of hydroquinone were added, and the mixture was reacted at 118°C for 6 hours. After vacuum distillation, rust inhibitor A was obtained; Step 2: 4 parts of tannic acid, 0.24 parts of triphenylphosphine, 0.016 parts of hydroquinone, and 12 parts of ethyl acetate were mixed evenly, 10 parts of glycidyl methacrylate were added, and the mixture was reacted at 90°C for 23 hours. After purification and drying, tannic acid containing double bonds was obtained; Step 3: Evenly mix 10 parts of styrene, 3 parts of acrylic acid, 5 parts of rust inhibitor A, 4 parts of double-bond tannic acid, 12 parts of 2-hydroxyethyl methacrylate, 7 parts of methyl methacrylate and 5 parts of butyl acrylate, add 2 parts of ammonium persulfate and mix evenly to obtain a mixture; evenly mix 60 parts of deionized water and 0.4 parts of a composite emulsifier, heat to 78°C, dropwise add 1 / 3 of the mixture by mass, drip it over 35 minutes, and react for 0.8 hours; continue to dropwise add the remaining mixture, drip it over 2.5 hours, react at 88°C for 2.5 hours, cool to 50°C, neutralize with triethylamine, filter, and obtain a modified acrylic resin; the composite emulsifier is a mixture of sodium lauryl sulfate and OP-10 in a mass ratio of 1:1.5; Step 4: Mix 55 parts of modified acrylic resin and 15 parts of deionized water, add 0.15 parts of dimethylethanolamine, 0.2 parts of dispersant, 0.15 parts of defoaming agent, 0.2 parts of leveling agent, 2 parts of film-forming aid, 5 parts of barium sulfate, and 12 parts of mica iron oxide and mix evenly to obtain a water-based acrylic resin-based rotor rust inhibitor.

[0028] Comparative Example 3 is based on Example 2. In Comparative Example 3, the rust inhibitor B is replaced with double-bond tannic acid of the same mass. The remaining process steps and reaction parameters are consistent with those of Example 2.

[0029] Experiment: The water-based acrylic resin-based rotor rust inhibitor obtained in Examples 1-3 and Comparative Examples 1-3 was applied to a polished tinplate to a thickness of 25 μm. The sample was then baked in an 80°C oven for 30 minutes and then in a 150°C oven for 30 minutes to prepare a sample. The performance of the sample was tested and the test results were recorded: Adhesion testing was conducted in accordance with GB / T 9286-2021, "Paints and Varnishes Cross-Cut Test." Adhesion was measured using a crosshatch knife, and the cut area was visually inspected for rating. Grade 0: Completely smooth cut edges with no shedding within the grid. Grade 1: Slight shedding of coating at the intersection of the cuts, but the affected cross-cut area was no more than 5%. Grade 2: Shedding of coating at the intersection of the cuts and / or along the edges, with the affected cross-cut area exceeding 5% but no more than 15%. Salt spray resistance testing was conducted in accordance with GB / T 10125-2021, "Artificial Atmosphere Corrosion Test, Salt Spray Test." The chamber temperature was 35°C, and the test solution was a 5% by mass NaCl solution. Rust resistance testing: The specimens were placed at 50°C and 65% humidity for 50 hours, and the rust area on the specimen surface was measured. Water contact angle testing: 2µL of deionized water was used for the test. All tests were repeated three times and the average value was obtained.

[0030] The test results are shown in Table 1.

[0031] Table 1 Test results of relevant properties of water-based acrylic resin-based rotor rust inhibitor

[0032] Combining Examples 1-3 with Comparative Examples 1-3 demonstrates that the water-based acrylic resin-based rotor rust inhibitor prepared by the present invention exhibits excellent rust resistance and adhesion, as well as superior corrosion resistance and hydrophobicity. By combining Rust Inhibitor A and Rust Inhibitor B in the water-based acrylic resin, a synergistic effect is achieved, not only enhancing the overall performance of the rust inhibitor but also enabling it to better withstand corrosion challenges in diverse environments, providing more comprehensive protection.

[0033] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.

Claims

1. A method for processing a water-based acrylic resin-based rotor rust inhibitor, characterized by: The steps include: Step 1: 1-(2-hydroxyethyl)-2-oleic acid imidazoline, perfluoropolyether carboxylic acid and toluene are uniformly mixed, p-toluenesulfonic acid and hydroquinone are added, and the mixture is reacted at 115-120° C. for 5-7 hours, and then distilled under reduced pressure to obtain rust inhibitor A; Step 2: Disperse the double-bond tannic acid in deionized water, stir for 10-20 minutes, add the mixed solution of phosphoric acid and penetrant, and stir evenly to obtain a modified tannic acid solution; Dispersing carbon nanotubes in a modified tannic acid solution, ultrasonically dispersing for 2-3 hours, centrifuging, and drying to obtain a rust inhibitor B; Step 3: Styrene, acrylic acid, rust inhibitor A, rust inhibitor B, 2-hydroxyethyl methacrylate, methyl methacrylate and butyl acrylate are mixed evenly, and ammonium persulfate is added and mixed evenly to obtain a mixture; deionized water and a composite emulsifier are mixed evenly, the temperature is raised to 75-80° C., 1 / 3 of the mixture by mass is added dropwise, the mixture is added over 30-40 minutes, and the reaction is carried out for 0.5-1.0 hours; the remaining mixture is added dropwise over 2-3 hours, the reaction is carried out at 85-90° C. for 2-3 hours, the temperature is lowered to 45-55° C., triethylamine is used for neutralization, and filtering is carried out to obtain a modified acrylic resin; Step 4: Evenly mix the modified acrylic resin and deionized water, add dimethylethanolamine, dispersant, defoaming agent, leveling agent, film-forming aid, barium sulfate, and mica iron oxide, and mix evenly to obtain a water-based acrylic resin-based rotor rust inhibitor.

2. The method for processing a water-based acrylic resin-based rotor rust inhibitor according to claim 1, characterized in that: In step 1, the mass ratio of the 1-(2-hydroxyethyl)-2-oleic acid imidazoline, perfluoropolyether carboxylic acid, and toluene is 1:(1.5-3.0):(3-5).

3. The method for processing a water-based acrylic resin-based rotor rust inhibitor according to claim 2, characterized in that: The preparation steps of the 1-(2-hydroxyethyl)-2-oleic acid imidazoline are as follows: oleic acid, hydroxyethylethylenediamine and xylene are uniformly mixed, reacted at 150-160° C. for 5-7 hours, and then heated to 210-220° C. for 3-5 hours to obtain 1-(2-hydroxyethyl)-2-oleic acid imidazoline.

4. The method for processing a water-based acrylic resin-based rotor rust inhibitor according to claim 1, characterized in that: In step 2, the mass ratio of the double-bond tannic acid, deionized water, phosphoric acid and penetrant is 1: (25-50): (1-2): (0.01-0.03).

5. The method for processing a water-based acrylic resin-based rotor rust inhibitor according to claim 4, characterized in that: The preparation steps of the double-bond tannic acid are as follows: tannic acid, triphenylphosphine, hydroquinone and ethyl acetate are uniformly mixed, glycidyl methacrylate is added, and the mixture is reacted at 85-95° C. for 22-24 hours. After purification and drying, the double-bond tannic acid is obtained.

6. The method for processing a water-based acrylic resin-based rotor rust inhibitor according to claim 1, characterized in that: In step 2, the mass ratio of the carbon nanotubes to the modified tannic acid solution is 1:(30-50).

7. The method for processing a water-based acrylic resin-based rotor rust inhibitor according to claim 1, characterized in that: In step 3, the amounts of the components are as follows: 8-12 parts of styrene, 2-4 parts of acrylic acid, 4-6 parts of rust inhibitor A, 3-5 parts of rust inhibitor B, 10-15 parts of 2-hydroxyethyl methacrylate, 5-8 parts of methyl methacrylate, 4-6 parts of butyl acrylate, 1-3 parts of ammonium persulfate, 50-70 parts of deionized water, and 0.2-0.6 parts of composite emulsifier.

8. The method for processing a water-based acrylic resin-based rotor rust inhibitor according to claim 7, characterized in that: The composite emulsifier is prepared by uniformly mixing sodium lauryl sulfate and OP-10 in a mass ratio of 1:(1-2).

9. The method for processing a water-based acrylic resin-based rotor rust inhibitor according to claim 1, characterized in that: The water-based acrylic resin-based rotor rust preventive comprises the following raw materials: by weight, 50-60 parts of modified acrylic resin, 10-20 parts of deionized water, 0.1-0.2 parts of dimethylethanolamine, 4-6 parts of barium sulfate, 10-15 parts of mica iron oxide, 0.1-0.3 parts of dispersant, 0.1-0.2 parts of defoaming agent, 0.1-0.3 parts of leveling agent, and 1-3 parts of film-forming aid.

10. A water-based acrylic resin-based rotor rust inhibitor prepared according to the processing method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-gloss metal anti-rust paint and preparation method thereof

    CN102993792A

  • Ultraviolet curing paint based on carbon nanotubes and preparation method of ultraviolet curing paint

    CN106634089A

  • Antirust acrylate emulsion and preparation method thereof

    CN111234078A

  • Corrosion-resistant solder paste plastic tank and preparation method thereof

    CN116554574A

  • Preparation process of environment-friendly degradable corrosion-resistant sealing grease

    CN118853263A